Investigation of the relationship between burned areas and climate factors in large forest fires in the Çanakkale region - Ertuğrul, Mertol; Özel, Halil Barış; Varol, Tuğrul; Cetin, Mehmet; Sevik, Hakan; Varol, Tuğrul; Özel, Halil Barış; Ertuğrul, Mertol (Springer, 2019)
Fires pose a serious threat to the forests that lay on the western and southern coastline of Turkey that start with North Aegean coasts and end with the provincial boundaries of Hatay. canakkale, a western province of Turkey, is located in the North Aegean boundary and its topography (Dardanelles Strait), climate, and vegetation cover combine to form an inviting recipe to forest fires. Although the province is located in a transitional zone in terms of climate and vegetation, each year it witnesses highly dry and hot fire seasons. Thus, large forest fires occur periodically. In this research, the relationship between the large periodic fires (larger than 100 ha) and the climate data was investigated, with a particular focus on the most severe 8 fire seasons from 1969 to 2007. We established that there is a relationship between 1977, 1985, and 1986 fire seasons and the climate data for the corresponding periods. The remaining 5 seasons in which conflagrations occurred were also found to coincide with the days with high daily severity indices (DSR). These are 1969, 1977, 1985, 1987, and 2008. Additionally, 2008 was determined as the year with the highest fire risk, followed by year 1969.
Keywords: Burned Area; Climate Factors; Daily Severity Index; Forest Fires; Seasonal Severity Index